Mapping of Families at Risk of Stunting Based on Four Too Factors in South Kalimantan - Norma Yuni Kartika; Lina Suherty; Sopyan Sopyan; Galuh Bayuaji; Nur Hidayah; Chintania Azahra Tantri Noermartanto (Jurnal Geografika (Geografi Lingkungan Lahan Basah), 2023)
Stunting is a condition of failure to thrive in children under five, the impact of chronic malnutrition in the first 1,000 days of life. Stunting is caused by multiple determinants, including the mother's age during pregnancy is too young or too old, the distance between pregnancies is too close, and too many children besides other determinants. The prevalence of stunting in South Kalimantan in 2021 is 30%, which is still far from the achievement target set by the government, which is at least 14% in 2024. The purpose of this paper is to map families at risk of stunting based on four too factors in South Kalimantan. This research uses a quantitative method sourced from secondary data, namely data on families at risk of stunting as a result of updating, verifying, and validating Family Data Collection 2021 (PK21) data in South Kalimantan. Data analysis in this study used: (1) descriptive statistical analysis to describe families at risk of stunting with 4 (four) too factors; (2) calculating the classification; (3) mapping; (4) conclusion. Four too factors is a factor that causes stunting in children because they can affect the parenting style of parents towards their children, so that, to take good care of children, fulfilling nutrition in children cannot be done optimally which will cause children to be stunted. In addition, if the mother gives birth at a distance of > 2 years, the mother does not have time to prepare the mother's condition and nutrition for the next pregnancy, thus affecting the fetus she is carrying.